Parametrical method of low-frequency harmonics suppression in rectifier’s output voltage under supply voltage unbalances (Mathematical model, study and industrial application) - Ali Zada, P.; Tuncay, N.; Ozturk, B.; Kivanc, C.; Mamedov, H.A.; Abdullaev, S.A. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2016)
This paper deals with using an original and pure electronic method for low-frequency harmonic suppression with wide industrial realization and application, in place of the usually heavy inductive, low-frequency harmonic filters. One of the main applications was made for small land power supply units of onboard complexes in ground-based air navigation when preflight ground check-service is made. The transport management at thousands of small provincial airports in the former country is still unfortunate. The same situation is in Northern and central Central Asia, Northern Caucasian and Trans-Caucasian Mountains, oriented to small civil and agricultural services airports, etc. Everywhere the phase and line voltage amplitude unbalance can reach between 10-15% at the settlement’s power tiny transformer or generator and there are thousands and thousands of such local «airports» [1, 6]. This paper has been editing by a native speaker, Ms. Rachel Alcorn — our sincere thanks. У статті розглядається використання оригінального і чисто електронного методу низькочастотного зниження рівня гармонік для широкої промислової реалізації та застосування в якості індуктивних низькочастотних фільтрів гармонік. Одним з основних застосувань методу було здійснено для невеликих блоків живлення бортових комплексів наземного базування повітряної навігації при проведенні передпольотної наземної перевірки та обслуговування. Управління транспортом у великій кількості невеликих провінційних аеропортів проводилося невдало. Та ж ситуація спостерігається в північній і центральній частині Середньої Азії, Північного Кавказу і Закавказьких гір, які орієнтовані на невеликі аеропорти цивільних і сільськогосподарських послуг і т.д. Скрізь в локальних аеропортах дисбаланс фази і амплітуди напруги в лініях може досягати 10-15% при включенні живлення невеликого трансформатора поселення або генератора [1, 6]. Висловлюємо подяку за редагування статті пані Рейчел Алкорн.